Mass-culture technique of a South African Heterorhabditis bacteriophora isolate, using in vitro liquid culture - Claasen, Nicholle; Dunn, Murray D; Malan, Antoinette P. (African Entomology, 2025)
Heterorhabditis bacteriophora is an entomopathogenic nematode (EPN), and together with its mutualistic bacteria, is a highly effective insect biocontrol agent. The preferred method for large-scale production involves in vitro liquid culture, whereby the nematode and bacteria are cultivated in an artificial medium that replicates the haemocoel conditions found within the insect host. Although the mass-culturing method for H. bacteriophora has proven successful in other countries, it has still to be implemented as a local commercial product in South Africa, despite its considerable potential for pest control. Several factors impact on the success of an in vitro liquid culture, including the bacterial inoculum density and the ingredients used in the culture media. Thus, this study aimed to develop an in vitro liquid culture protocol for a local isolate of H. bacteriophora. Switching from soy powder to egg yolk powder significantly increased the yield of infective juveniles (IJ) during culture, despite there being no differences in IJ recovery between days 2 to 4 after nematode inoculum. Furthermore, the bacterial inoculum density exerts a significant influence on recovery and yield, with the use of a 2% (v/v) inoculum concentration showing the most favourable results. Bacterial cell density is crucial for IJ recovery, as it provides the food signal that activates the IJ. The success obtained with this liquid culture technique for H. bacteriophora paves the way for the optimisation of various additional liquid culture parameters, including nutrients levels, oxygen concentrations and cost-effective ingredients.